Fully illuminated Jupiter disk albedo and limb darkening observed by DSCOVR-EPIC from the Earth–Sun Lagrange-1 orbit - Herman, Jay; Blank, Karin (Frontiers in Remote Sensing, 2026)
Multispectral images of Jupiter were obtained by the Earth polychromatic imaging camera (EPIC) orbiting at the Earth–Sun Lagrange point 1 (L1) on 15 March 2016 and again on 5 June 2019 using a 30-cm Cassegrain telescope imaging on a 2,048 × 2,048 pixel detector with a 0.62° field of view. The images of Jupiter were obtained using 10 narrow bandpass filters (in the range of 317.5–779.5 nm) that were radiometrically calibrated and designed to have very little out-of-band transmissions. The EPIC instrument was carefully corrected for geometric stray-light effects, pixel non-uniformity (flat fielding), and etaloning (680–780 nm). The Jupiter images were contained in a small disk of diameter 43 pixels near the center of the detector. The resulting images had a spatial resolution of 4,900 km as well as showed clear evidence of limb darkening, the east-west bands, and the red spot of Jupiter. These results were compared with previous measurements from Jupiter filter images obtained by the Hubble space telescope from a ground-based filter instrument at the Tortugas Mountain Observatory operated by New Mexico State University and the portable filter device PlanetCam at Calar Alto Observatory in Spain. The EPIC estimates of the whole-disk albedo are in good agreement with previous high-spectral-resolution spectrometer results (from the European Southern Observatory in La Silla, Chile) in the visible and near-infrared wavelengths but are lower in five ultraviolet (UV) narrow bandpass filter channels (318–388 nm). A possible reason for this disagreement with the spectrometer-estimated UV albedo could be out-of-band stray light from the spectrometer grating. The EPIC observations from L1 have better spatial resolution than ground-based filter measurements and are expected to provide improved estimates of Jupiter’s limb darkening. Absorption by methane was considered during the measurements, and the current mixing ratio 2 × 10−3 is estimated to be insufficient to explain the decrease in albedo between 764 and 779.5 nm unless the reflecting cloud layer is at a pressure of two atmospheres.